Achieving the lightweight wear-resistant TiC reinforced AlFeCrCo medium-entropy alloy coating on Mg alloy via resistance seam processing. (15th March 2022) - Zhao, Dechao; Kong, Decheng; Huang, Jie; Wang, Mingliang; Yamaguchi, Tomiko; Wang, Haowei
Abstract: The enhancement of wear resistance is a long-last changeling problem required by advanced application of Mg alloys. Herein, the lightweight TiC reinforced AlFeCrCo medium-entropy alloy (MEA) composite coating was firstly fabricated on Mg alloy via resistance seam processing. The coating was consisted of a BCC-based MEA matrix and TiC particles, in which a small amount of Mg (<5wt.%) penetrated into coating gaps. A good bonding between the coating and Mg alloy was formed, and such interface belonged to a semi-coherent relationship. Furthermore, a coherent interface between the MEA matrix and TiC was revealed with the crystallographic orientation relationships. Due to these well-bonded characteristics and reinforcing effects from TiC, this composite coating exhibited superior wear resistance by adhesive wear and oxidative wear. This work not only expanded the applicable types of coating materials, but also provided a novel method for preparing lightweight wear-resistant composite coating on Mg alloys. Graphical abstract: Image, graphical abstract